2023
DOI: 10.1186/s12903-023-02706-8
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in 3D auto-filling alveolar cleft of CT images to assess the influence of alveolar bone grafting on the development of maxilla

Abstract: Background Machine learning based auto-segmentation of 3D images has been developed rapidly in recent years. However, the application of this new method in the research of patients with unilateral cleft lip and palate (UCLP) is very limited. In this study, a machine learning algorithm utilizing 3D U-net was used to automatically segment the maxilla, fill the cleft and evaluate the alveolar bone graft in UCLP patients. Cleft related factors and the surgery impact on the development of maxilla we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Deep learning has been widely applied in medical image identification, segmentation, and registration due to its promising performance with high precision and efficiency (Xu et al, 2022). Deep learning-based methods have been successfully implemented to segment 3D maxillofacial anatomical structures, such as teeth (Cui et al, 2022), mandible , maxillae (Zhang et al, 2023), zygoma bone (Tao et al, 2023), and maxillary sinuses (Xu et al, 2020) from CBCT images. It has been reported that human radiologists obtained a lower accuracy and segmentation efficiency in teeth and alveolar bone segmentation than in deep learning models (Cui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning has been widely applied in medical image identification, segmentation, and registration due to its promising performance with high precision and efficiency (Xu et al, 2022). Deep learning-based methods have been successfully implemented to segment 3D maxillofacial anatomical structures, such as teeth (Cui et al, 2022), mandible , maxillae (Zhang et al, 2023), zygoma bone (Tao et al, 2023), and maxillary sinuses (Xu et al, 2020) from CBCT images. It has been reported that human radiologists obtained a lower accuracy and segmentation efficiency in teeth and alveolar bone segmentation than in deep learning models (Cui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%